Ternstroemia acajetensis (Pentaphylacaceae), a new species from the cloud forest in central Veracruz, Mexico - Castillo-Campos, Gonzalo; Palacios-Wassenaar, Olivia M. (Phytotaxa, 2019)
Ternstroemia acajetensis Cast.-Campos & Palacios-Wassenaar sp. nov. is described and illustrated. This new taxon is part of the arboreal and shrub strata of cloud forests, Quercus forests, and Pinus-Quercus forests in the mountains of the states of Veracruz, Puebla, and Oaxaca, Mexico. This species is related to T. sylvatica and T. huasteca, which grow in similar environments. However, the new species can be differentiated from the others by the length of the peduncle, the shape of the petals, the color of the flowers, and the length of the prolongation of the connective in the anthers.